Adopted son : Washington, Lafayette, and the friendship that saved the Revolution - Clary, David A. (New York : Bantam Books, 2007)
"They were unlikely comrades-in-arms. One was a self-taught, middle-aged Virginia planter in charge of a ragtag army of revolutionaries, the other a rich, glory-seeking teenage French aristocrat. But the childless Washington and the orphaned Lafayette forged a bond as strong as any between father and son, a trust that saw them through betrayals, shifting political alliances, and the trials of war. Their friendship continued throughout their lives. Lafayette inspired widespread French support for a struggling young America and personally influenced Washington's antislavery views. Washington's enduring example as general and statesman guided Lafayette during France's own revolution years later. Using personal letters and other key documents, author Clary offers a rare glimpse of the American Revolution, including intimate portraits of such major figures as Alexander Hamilton, Benedict Arnold, and Benjamin Franklin. The result is a remarkable, little-known epic of friendship, revolution, and the birth of a nation.--From publisher description."--From source other than the Library of Congress
Includes bibliographical references and index.
900-999
Keywords: Washington, George, -- 1732-1799 -- Friends and associates; Washington, George, -- 1732-1799.; Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834.; Lafayette, Marie Joseph Paul Yves Roch Gilbert Du Motier, -- marquis de, -- 1757-1834 -- Friends and associates; Presidents -- United States -- Biography; Statesmen -- France -- Biography; United States -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Biography; Biographies. -- Nonfiction